Satire Humor in the Children's Cartoon Series Spongebob Squarepants by Stephen Hillenburg - Dwi Putra, RD. Ferdiansyah Aprillianto; Hestiana, Siska; Pertala, Erik Candra (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
The title of this is satirical humor in the childrens cartoon series Spongebob Squarepants. The purpose of this study is to show and explain the scenes containing satirical humor in this cartoon that has been shown to many underage audiences who do not understand what the humor means. In this study, researchers used a descriptive qualitative method and used an objective approach by focusing on the object itself, namely “Spongebob Squarepants” cartoon. Then in collecting data, the researcher uses the listening technique in which the author has watched and listened to this cartoon repeatedly so as to get what will be presented in this study. The results of this study show several scenes containing satirical humor in the Spongebob Squarepants cartoon, which are shown to underage audiences and also explain the depiction of the humor that has been found. Keywords: Satirical Humor, Cartoon, Spongebob Squarepants